Commentary: A Myriad Aberrations on Information of Ontogeny of Drug Metabolizing Enzymes in the Pediatric Population: An Obstacle for Personalizing Drug Therapy in the Pediatric Population - Rao S. Uppugunduri, Chakradhara; Ansari, Marc (Drug Metabolism Letters, 2016)
Major lacunae exist in our understanding of how developmental changes in drug biotransformation influence drug’s exposure and thus its efficacy and toxicity in children. It is not just about smaller weight in children, which modifies the pattern of the drug's exposure. There are developmental, functional changes in organ systems, liver to body mass ratios, and changes in metabolism. Understanding these changes and conducting studies to obtain data on ontogeny of drug metabolizing enzymes is essential for implementation of personalized dosing schedules in the pediatric population.
Keywords: enzyme